Causal Effects of Educational Mismatch in the Labor Market - Jan Kleibrink (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
This paper analyses the causal effects of educational mismatch on wages, individual health and job satisfaction. As educational mismatch is subject to unobserved heterogeneity in all of these fields, different identification strategies are applied to derive causal effects. In the wage regressions, an FE model is estimated and new instrumental variables are introduced. Results show that the causal effects of educational mismatch are less severe than the majority of the literature has found when not controlling for unobserved heterogeneity. In the analysis on health and satisfaction effects, causality is achieved by differentiating between overeducated workers after a firm closure and those overeducated for other reasons. The results show that there are no causal effects of educational mismatch on any of these variables.
Keywords: I21; J31; I10; 330